The effect of motivational interviewing techniques on the knowledge level of asthma control among mothers of children with allergic asthma - Karhan, Esra Rusen; Soylar, Pinar (Elsevier Science Inc, 2024)
Purpose: This study aims to evaluate the effect of education given with motivational interviewing techniques on mothers of children with allergic asthma aged 4 -11 years on asthma control and knowledge level. Methods: The research was designed according to the CONSORT checklist with a randomized controlled design. 76 participants were randomly assigned to either an intervention ( n = 38) or control group (n = 38). The intervention group received asthma education utilizing motivational interviewing techniques from a pediatric nurse. The control group received no further education. The Childhood Asthma Control Test and Asthma Knowledge Level Questionnaire were used to collect data. The control group received only education at the time of discharge. Results: The mothers' asthma control and asthma knowledge scores in the experimental group were significantly higher than in the control group ( p < 0.001). In the experimental group, asthma control scores increased from 14.29 + 4.27 to 21.37 + 1.57 after education. The mean score of the asthma knowledge score increased from 54.74 + 10.89 to 73.47 + 7.17 after intervention. Conclusions: The study showed that education using motivational interviewing techniques for mothers of children with allergic asthma increased their knowledge and positively affected asthma control. Implications to practice: Education is important in improving mothers' knowledge about allergic asthma. Asthma education using motivational interviewing techniques should be provided when their children are newly diagnosed. Education practices should be implemented as a policy in hospitals and pediatric clinics, and nurses should be supported in ensuring the implementation of education practices. (c) 2024 Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Available online xxxx; Asthma; Children; Education; Nursing; Motivational interviewing